Effect of Macroeconomic Indicators on the Composite Stock Price Index With the VECM Approach - Dalimu, Aan Rivaldy; Satria, Dias (Journal of Development Economic and Social Studies, 2025)
The Indonesian capital market, represented by the Composite Stock Price Index (IHSG), serves as a crucial barometer reflecting the national economic condition and market participants' perceptions of macroeconomic variables such as inflation, the USD/IDR exchange rate, interest rates, and money supply (M2). This study aims to analyze the influence of these macroeconomic variables on changes in the IHSG during the 2019–2025 period using the Vector Error Correction Model (VECM) approach. The results indicate that only the money supply (M2) variable significantly affects IHSG changes both in the long and short term. Inflation, exchange rate, and interest rate variables do not show significant effects on IHSG. These findings suggest that monetary liquidity plays a central role in the dynamics of the Indonesian stock market during the study period, hence monetary policy management should focus on supporting capital market stability. This study recommends that investors and policymakers pay close attention to developments in the money supply as a key indicator in investment decision-making and economic policy formulation.